A Feast of Senses: Rhetorical Devices in the Prose of Salman Rushdie with Special Reference to Metaphors and Adverbs - Swan, Toril (Nordlit, 1999)
The paper analyzes Rushdie's rhetorical use of adverbials and metaphors, in particular his rhetorical use of adverbials. The adverbs in question function rhetorically in three, partly overlapping ways. They are frequently metaphorical, and even if strictly literal (i.e. concrete), convey images and sense forms. Secondly, the linking and focusing function of the adverbs is an effective rhetorical device, as prototypical adverb use - focus on or specification of verbal actions and activities - is transformed into a focus on or specification of the subject, while the adverb form (the -ly suffix) ensures a simultaneous link to the verbal action. Finally, Rushdie's adverbs function rhetorically as abbreviated propositions. This use of adverbs is in particular a property of English, and Rushdie exploits it elegantly.